Bibliometric analysis of research trends and networks in carbon tax studies: Insights into environmental and economic policy implications - Andi Kusumawati; Suhanda Suhanda; Darmawati; Andi Iqra Pradipta Natsir; Indira Syakira Kirana Juanda (Environmental Economics)
Carbon taxes are increasingly recognized as a critical tool in mitigating climate change by reducing carbon emissions. This study analyzes research trends in carbon tax studies using bibliometric techniques and social network analysis to explore their environmental and economic impacts and policy implications. By analyzing 922 documents from 308 sources published between 1968 and 2024, the study identifies key topics, emerging trends, and collaboration patterns among researchers. The results show a significant increase in carbon tax publications and citations, particularly from 2000 to 2019, peaking around 2017–2019, followed by a decline after 2021. The most frequently studied topics include carbon tax effects on emissions reduction, economic balance, and environmental sustainability. Social network analysis reveals influential researchers and institutions driving the discourse on carbon taxes, highlighting the importance of interdisciplinary collaboration in shaping effective policies. These findings provide insights into the evolution of carbon tax policies and underscore the need for continued research on specialized themes such as the role of carbon taxes in supply chain management, social equity, and energy policy. AcknowledgmentsThe authors would like to express their sincere gratitude to the Rector and the Dean of the Faculty of Economics and Business, Hasanuddin University for their unwavering support and invaluable assistance in this analysis. Their commitment to advancing academic research and community service has been instrumental in completing this study.